Spreading Modes on Copper and Steel Surfaces; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Feoktistov D. V. Dmitriy Vladimirovich (2016, 2016)
Title screen